2016
DOI: 10.1016/j.lfs.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 contributes to the hypoxia-mediated regulation of actin cytoskeleton in cerebrovascular smooth muscle

Abstract: Ischemia/reperfusion and the resulting oxidative/nitrative stress impair cerebral myogenic tone via actin depolymerization. While it is known that NADPH oxidase (Nox) family is a major source of vascular oxidative stress; the extent and mechanisms by which Nox activation contributes to actin depolymerization, and equally important, the relative role of Nox isoforms in this response is not clear. Aim To determine the role of Nox4 in hypoxia-mediated actin depolymerization and myogenic-tone impairment in cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Reactive nitrogen species may be involved as it has been recently reported that S-nitrosation of cysteine 141, a conserved cysteine residue in many species, induced sEH activity in H9c2 cells and increased sEH activity was correlated with endogenous sEH nitrosation after ischemia/reperfusion injury in mice (19). Interestingly, NOX4 and inducible nitric oxide synthase were significantly upregulated after hypoxia and ischemia/reperfusion injury (16) and inhibition of iNOS markedly reduced myocardial infarct size in mice after LAD ligation (71). It is noteworthy that cis allelic variants of sEH gene Ephx2 segregated with heart failure, with increased transcript, protein, and enzyme activity (45).…”
Section: Discussionmentioning
confidence: 98%
“…Reactive nitrogen species may be involved as it has been recently reported that S-nitrosation of cysteine 141, a conserved cysteine residue in many species, induced sEH activity in H9c2 cells and increased sEH activity was correlated with endogenous sEH nitrosation after ischemia/reperfusion injury in mice (19). Interestingly, NOX4 and inducible nitric oxide synthase were significantly upregulated after hypoxia and ischemia/reperfusion injury (16) and inhibition of iNOS markedly reduced myocardial infarct size in mice after LAD ligation (71). It is noteworthy that cis allelic variants of sEH gene Ephx2 segregated with heart failure, with increased transcript, protein, and enzyme activity (45).…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, Nox1, Nox2 and Nox4 were detected in human brain vascular smooth muscle cells [63]. In basilar arterial endothelial cells, Nox1 and Nox4 mRNA are highly expressed, whereas Nox2 transcript is expressed to a far lesser extent [61].…”
Section: Cerebral Microcirculationmentioning
confidence: 99%
“…Our findings showing the inhibitory effect of tyrosine nitration of p85 subunit resulting in vascular cell death lend further support to prior reports that showed the inhibitory effect of tyrosine nitration of p85 subunit and vascular cell death in oxygen-induced retinopathy [ 11 ] and nitration of p85 in brain of diabetic animals [ 24 ]. Additional targets were identified, including tyrosine nitration and inhibition of the nerve growth factor (NGF) survival receptor, TrkA, resulting in neurodegeneration in experimental diabetes [ 12 , 34 ] and nitration of actin, resulting in loss of vascular tone in smooth muscles [ 35 ]. These results confirm the relationship between nitration of p85, the decreases in Akt activity, and the proapoptotic effects of high glucose and peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%